EXPLORING GENERATION Z’S BEHAVIORAL INTENTION TO USE SKYSCANNER: THE ROLE OF PERCEIVED EASE OF USE, PERCEIVED USEFULLNES, AND TRUST - Adipura Danang Maulana; Nova Almas Nabila (INDONESIAN JOURNAL OF BUSINESS AND ECONOMICS, 2025)
The development of information technology has changed the way people search and purchase airplane tickets. This study aims to analyze the effect of Perceived Ease of Use, Perceived Usefulness, and Trust on Behavioral Intention to Use the Skyscanner application for Generation Z in Yogyakarta. Using a quantitative approach, this study involved 100 student respondents selected through purposive sampling technique. Data were analyzed using multiple linear regression with the help of SPSS. The results showed that the three independent variables-Perceived Ease of Use (β=0.720), Perceived Usefulness (β=0.724), and Trust (β=0.708)-partially and simultaneously had a positive and significant effect on Behavioral Intention to Use with a coefficient of determination of 80.4%. These findings strengthen the Technology Acceptance Model (TAM) in the context of airfare comparison applications and emphasize the importance of ease of use, practical benefits, and trust in increasing technology adoption among Generation Z. The practical implication for application developers is the need to focus on intuitive interfaces, efficient features, and data security transparency to increase the intention to use airfare search applications.